A study on the allergic reaction to plaster of Paris, acrylic monomer, pumice and eugenol - Pangilinan, Ma. Cristina R.; Pordesimo, Toniet O.; Gonzalez, Angela (Adviser).; Ortega, Adelwisa (Adviser).
Four dental materials, plaster of Paris, acrylic monomer, pumice and eugenol, were tested for their allergenicity among the senior clinicians and freshmen students of the University of the Philippines College of Dentistry during the school year 1987-1988. Subjects were grouped into those with allergic predisposition and those without allergic predisposition with the aid of a questionnaire. Those without allergic predisposition were further classified into those with minimal exposure to the test materials and those with prolonged exposure. Patch testing was performed on the sample population. The incidence of a positive reaction was found to be greater among those with allergic predisposition than among those without. The value obtained for plaster of Paris, acrylic monomer and eugenol were 14.3% and 10.7% for those with and without allergic predisposition, respectively. Pumice elicited 10.7% incidence of positive reaction among predisposed individuals and 3.6% among those without predisposition. Among individuals without allergic predisposition, the incidence of allergic reaction to plaster and eugenol was 14.3% for subjects with prolonged exposure and 7.1% for those with minimal exposure. Acrylic monomer gave 21.4% and 14.3% respectively. For pumice, incidence rate for those with minimal exposure was 17.1% and 0 for those with prolonged exposure.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Plaster of Paris; Acrylic monomer